Explaining the Low Primary School Performance in the Rural District of Black River, Mauritius: A Teacher’s Perspective - Appavoo, Perienen (Journal of Education and Research, 2015)
Pass rates at the end of primary schooling for the rural district of Black River are alarming as they have remained at a low level over many years. This research seeks to explain the situation from a teacher’s perspective and to unveil the causes which persistently hamper student progress. Statistics show that children in Black River are on a par with their counterparts in other rural and urban areas in respect to access to school facilities, qualified teachers, and provision of pedagogical materials and learning tools.  This study shows that students’ motivation, follow-up of learning at home and parents’ involvement in children’s studies are at an unacceptable level and require urgent consideration. The last two determinants were found to be positively related but the correlation coefficient is not very high (r = 0.518). Analysis also points to the low and inadequate level of pre-primary education of children when they enter primary schools, and to the difficulties of teachers in educating children with social problems. One seminal finding of this research study is that, without sustained parent/community support and encouragement, learning performance in the Black River region is unlikely to be improved.  This finding is in agreement with the results of many studies reported previously in the literature. Respondents made some valuable suggestions for remedying the situation, the most important one being the need to implement community-based strategies to encourage parents and the surrounding community to support the education of children.